Postcolonial madness : the representation of dictatorship in selected novels by Nuruddin Farah and Ngugi wa Thiong’o - (:unkn) unknown (My University, 2023)
This thesis offers a multidisciplinary reading of the madness of dictatorial regimes in Nuruddin Farah’s Sweet and Sour Milk, Sardines, and Close Sesame, and Ngugi wa Thiong’o’s Matigari and Wizard of the Crow. Indeed, we see that in these novels, the postcolonial world is governed by contradictions and paradoxes resulting from dictators’ abusive use of force, wealth, and persuasion, the three fundamental means of obtaining consent and obedience according to the American historian Carroll Quigley. However, it appears that although these methods of governance can produce submission in the form of silence, distortion, and madness in certain characters, they also generate acts of resistance in others. Through interacting strands of story, history, and theory, this study demonstrates how Farah and Ngugi’s thematic treatments of the tropes of silence, distortion, madness, and resistance in their novels reveal the intricacies of an African political scene where fear of repression is second nature, where rumors contradict both private truths and public lies, where dictators use propaganda and indoctrination to sell their illusions to the masses, and where resistance to tyranny is seen as an act of madness. In short, this thesis suggests that even though the two authors approach these subjects each in their own way, through realism, sarcasm, satire, or hyperbole, Farah and Ngugi depict characters, both rulers and ruled, trapped in an inescapable spiral in which it is as much insane to resist tyranny as to submit to it.
Keywords: African Research